Benefits of Laser Beam Based Additive Manufacturing in Die Droduction - Öter, Zafer Çağatay; Coşkun, Mert; Akça, Yaşar; Sürmen, Ömer; Yılmaz, Mustafa Safa; Özer, Gökhan; Tarakçı, Gürkan; Koç, Ebubekir (Elsevier, 2019)
The aim of this study was to benefit from the novel design and production freedom of laser manufacturing in order to alter the existing design concept of extrusion dies and to resolve the limits in die production. A two-stage experimental study was carried out to reveal advantages of laser manufacturing on the performance and capabilities of aluminum extrusion dies. In the first stage, geometric forms of hot work tool steel dies used in aluminum extrusion were optimized for Direct Metal Laser Sintering (DMLS) by means of flow dynamics as well as surface quality and mechanical properties of the final part. Simple geometry profiles were extruded to investigate the product quality. In the second stage, dies were tested until failure to determine the performance and lifetime. Dies were produced using EOS M290 and were not subjected to any conventional finishing and/or surface hardening post processes. Field tests were carried out in an industrial aluminum extrusion facility and high-quality profiles were extruded. Dies and extruded profiles were characterized. Results revealed that DMLS can be a favorable method to produce dies having complex inner sections with high accuracy. Production of high quality extruded profiles was possible using additive manufactured dies directly from production.
Keywords: Aluminum Extrusion; Rapid Tooling; Die; Additive Manufacturing; Direct Metal Laser Sintering